Outcomes of Squamous Cell Carcinoma Oropharynx in Elderly Patients Treated with External Beam Radiation Therapy - A Retrospective Study from Tertiary Care Cancer Center - India - Ramanaiah, Kaluvoya; S, Sadanand; V V, Gautam; B, Mukesh; M, Sai Pranav; M,N, Arunkumar (Asian Pacific Journal of Environment and Cancer, 2024)
Background: Majority of Elderly patients with oro-pharyngeal Squamous cell (OPSCC) are treated with External beam Radiation Therapy(EBRT) alone, the benefit of chemotherapy after 70years is doubtful, we aim to analyze outcomes and morbidity in elderly OPSCC treated with EBRT. Methods: Retrospective study, all patients with Oropharyngeal squamous cell carcinoma histology, more than or equal 70 years of age, having performance status Eastern Cooperative Oncology Group (ECOG) 0-2, All stages other than metastatic disease, who were registered and treated with Radical radiation therapy alone at our institute from January 2015 to December 2018 were included. Having ECOG performance status 3-4, Patients treated with brachytherapy, or concurrent chemoradiation, synchronous primaries, re-irradiation are excluded from this study. Entire cohort of 30 patients (25 male, 5 female) were treated with EBRT, who received total dose 50Gy to 66Gy were included for analysis. Results: 90% of cases (27/30) were locally advanced (Stage III & IV), At median follow up duration of 18months (range 1 to 81 months), at 3, 4, and 5 years OS was 36.7% (95% Confidence interval (CI) = 19.4% - 54%), 23.3% (95% CI = 8.2% - 38.4%) and 19.4% (95% CI = 5.1 - 33.7%) respectively. Conclusion: compared to young, elderly OPSCC has poor outcomes, this subset may do as well as young people if treated with multi modality treatment with proper selection. By addressing the risk factors , using preventive measures, early detection , and ensuring access to the adequate health care facilities are pivotal in reducing the burden of cancer. Poor representations of this subset of population in clinical trails, facing challenges treating with multi modality approach may be one of the reason for poor outcomes compared to the young patients, needs prospective trails specifically focusing on this group of patients should be performed.